Minor Structures for the Improvement of Wave Disturbance in a Small Harbor - A. Sulis (Advances in Civil Engineering)
A very important aspect in the planning, design, and maintenance of a harbor is to determine the response of the harbor basin to incident waves. The Saras harbor in South Sardinia (Italy) has been experiencing significant wave disturbance that affects the safety of mooring and operational activities. In the framework of a large research, this paper summarises a comprehensive description of new energy absorbing structures that can be seen as an efficient alternative to more traditional structures when limited by economic or technical constraints. Specifically, the paper presents the results of a graphical preliminary approach and a numerical modelling that solves the enhanced Boussinesq equations in two horizontal dimensions.